Pseudophacocele following a Bicycle Handle Injury: A Case Report - Thakur, Sahil; Ichhpujani, Parul; Kumar, Suresh (Nepalese Journal of Ophthalmology, 2018)
Background: Pseudophacocele is a rare complication of blunt trauma in pseudophakic eyes.Case: We present a case of 60-year-old male who presented with pseudophacocele after injury from a bicycle handle. On presentation, visual acuity in the right eye was perception of light (PL) in 2 quadrants (superior and temporal) and left eye was 20/20. A PCIOL was seen superonasally in the right subconjunctival space with total hyphaema. Ultrasound demonstrated vitreous haemorrhage with membranes in right eye. We describe the surgical management and further clinical course of the patient.Conclusion: It is imperative to surgically manage these challenging cases. Despite optimum care visual outcomes are guarded in patients with severe blunt trauma.